Contributions of extension project about strengthening and expanding the obesity care line in the context of the COVID-19 pandemic - Ribeiro Ferreira , Ana Paula; Bezerra de Jesus , Cesar; Oliveira Valencio , Maria Eduarda; Farias Moreira , Daniela; Aparecida Silva Turini, Elaina; Dias Pires , Evelly; Luch do Santos , Julia; Ohnesorg de Souza Soares, Larissa; Santos Louro , Luana; Rocha Pompermayer, Vinicius Augusto; Trancoso Campos, Viviane (Guará Journal, 2022)
Obesity is a public health problem, and the COVID-19 pandemic has led to an increase in its risk factors. Despite the importance of the topic, managing obesity in primary care remains difficult. In this context, the outreach project "Strengthening and Expanding the Obesity Care Pathway in the Public Health System in Espírito Santo" aims to train primary and secondary care professionals on the management of individuals with obesity. METHOD: Events, training courses, social outreach, multidisciplinary team support in outpatient clinics, training sessions, and content dissemination on social media. RESULTS: The course received over 4,000 views; the social outreach activities saw significant community participation; the students' experience in outpatient clinics contributes to the academic development; the meetings provide theoretical foundations, and the social media content fosters continuing health education. DISCUSSION / CONCLUSIONS: The project fulfills its extension objective by enabling the exchange of knowledge, contributing to the continued training of health professionals, raising awareness among the population, and training students, by strengthening and expanding the line of care in obesity.
Keywords: Extension project; COVID-19; Obesity; Professional training; Primary care